2010
DOI: 10.4088/jcp.09m05019yel
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use and Risk of Recurrence in Bipolar Disorder

Abstract: Benzodiazepine use may be associated with greater risk for recurrence of a mood episode among patients with bipolar I and II disorder. The prescribing of benzodiazepines, at a minimum, appears to be a marker for a more severe course of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
1
32
2
3
Order By: Relevance
“…Moreover, BZDs are commonly used in the patients with newly diagnosed bipolar disorder despite not recommended in the clinical guideline. [6][7][8][9][10] In the study of Systematic Treatment Enhancement Program for BD, Perlis et al 45 reported that BZD use was associated with increased risk for recurrence of a mood episode among patients with bipolar 1 and 2 disorder. 45 Most guidelines have recommended different first-line, second-line, and third-line agents by different phases of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BZDs are commonly used in the patients with newly diagnosed bipolar disorder despite not recommended in the clinical guideline. [6][7][8][9][10] In the study of Systematic Treatment Enhancement Program for BD, Perlis et al 45 reported that BZD use was associated with increased risk for recurrence of a mood episode among patients with bipolar 1 and 2 disorder. 45 Most guidelines have recommended different first-line, second-line, and third-line agents by different phases of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] In the study of Systematic Treatment Enhancement Program for BD, Perlis et al 45 reported that BZD use was associated with increased risk for recurrence of a mood episode among patients with bipolar 1 and 2 disorder. 45 Most guidelines have recommended different first-line, second-line, and third-line agents by different phases of bipolar disorder. [6][7][8]46 However, this study investigated trends and patterns of pharmacological treatment among patients with newly diagnosed bipolar disorders in their first year of treatment and did not separate them by manic or mixed, depression, or maintenance phases.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year prevalence of BZD use among patients with BD with and without comorbid substance use disorder was reported to be 75% and 58%, respectively 81. Moreover, adjunctive BZD use at the time of symptom remission has been linked with higher risk of mood episode recurrence, as compared with no BZD use, in patients with BD-I and BD-II 82. However, some studies report no significant effect of BZD use on any outcome measure in patients with BD with comorbid anxiety or substance use disorders 83.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of acute settings, this approach is controversial due to the abuse liability and lack of controlled evidence about the long-term safety and effectiveness of benzodiazepines as adjuncts to foundational mood stabilizing medications such as lithium, selected anticonvulsants, and atypical antipsychotics (Brunette et al, 2003). Adjunctive benzodiazepine use at the time of symptom remission has been linked with higher risk of mood episode recurrence, as compared with no benzodiazepine use, in patients with bipolar I or II disorder (Perlis et al, 2010). On the other hand, effects of adjunctive benzodiazepines on core bipolar mood symptoms and associated symptoms such as anxiety and irritability have not been extensively investigated, and little is known about benzodiazepine treatment outcomes in bipolar disorder patients with comorbid anxiety and alcohol use disorders.…”
Section: Introductionmentioning
confidence: 99%